The effectiveness of essential oil extracted from alfalfa seeds for blood clotting - Hacini, Zineb; Boussebaa, Walid; Bourghra, Ibtisam; Habib, Ibrahim; Kendour, Zaouia; Debba, Zineb (European Journal of Chemistry, 2020)
The experiment was conducted on alfalfa seeds that were brought from Marjajah in the city of Touggourt. After the traditional extraction process, some of its physical properties were measured, including, refractive index, pH, with a yellowish green color, odor, prick, and transport value of 363 cm/S and on blood clotting. The results showed that the seed extract of alfalfa has an effect on blood clotting on the internal and external pathway by the prothrombin rate (TP) obtained that sample 1 has the largest clotting time of 22 seconds and by the time of cefalin kaolin (TCK), the highest coagulation time for sample 2 by 46 seconds. The prothrombin rate and the time of cefalin kaolin chronometer tests also show that alfalfa seed extract exercises an important anticoagulant activity compared to the two coagulation methods, because this activity is more pronounced towards the internal pathway that the external pathway passes, that is, the alfalfa seed extract is better than the normal witness and less than the positive witness heparin.